2015
DOI: 10.1371/journal.pone.0133549
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Understanding Algal Bloom-Mediated Fish Kills: The Role of Superoxide Radicals, Phycotoxins and Fatty Acids

Abstract: Quantification of the role of reactive oxygen species, phycotoxins and fatty acids in fish toxicity by harmful marine microalgae remains inconclusive. An in vitro fish gill (from rainbow trout Oncorhynchus mykiss) assay was used to simultaneously assess the effect in superoxide dismutase, catalase and lactate dehydrogenase enzymatic activities caused by seven species of ichthyotoxic microalgae (Chattonella marina, Fibrocapsa japonica, Heterosigma akashiwo, Karenia mikimotoi, Alexandrium catenella, Karlodinium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(75 citation statements)
references
References 70 publications
2
65
0
Order By: Relevance
“…Comparable to these observations in the Chilean waters, only 10 cells ml −1 of P. verruculosa were enough to cause mortality of salmon in New Zealand (MacKenzie et al, 2011). There might be a few experimental conditions that can explain our findings: (1) gill cells were shortly exposed to P. verruculosa toxic compounds (1 h) compared to other studies (Dorantes-Aranda et al, 2015;Mardones et al, 2015). Mardones et al (2015) showed that some strains of the toxic dinoflagellate Alexandrium catenella were able to reduce gill cell viability down to 20% of controls at 4,000 cells ml −1 after 2 h exposure due to net K + efflux from fish gill cells (Mardones et al, 2018).…”
Section: Lytic Activity Of P Verruculosasupporting
confidence: 45%
See 1 more Smart Citation
“…Comparable to these observations in the Chilean waters, only 10 cells ml −1 of P. verruculosa were enough to cause mortality of salmon in New Zealand (MacKenzie et al, 2011). There might be a few experimental conditions that can explain our findings: (1) gill cells were shortly exposed to P. verruculosa toxic compounds (1 h) compared to other studies (Dorantes-Aranda et al, 2015;Mardones et al, 2015). Mardones et al (2015) showed that some strains of the toxic dinoflagellate Alexandrium catenella were able to reduce gill cell viability down to 20% of controls at 4,000 cells ml −1 after 2 h exposure due to net K + efflux from fish gill cells (Mardones et al, 2018).…”
Section: Lytic Activity Of P Verruculosasupporting
confidence: 45%
“…Despite this, research on the toxic compounds produced by this species is incipient and has proven to be difficult. The fish cell line RTgill-W1 assay has been widely used to assess cell viability in ichthyotoxic-microalgal studies (Dorantes-Aranda et al, 2015). In this work, we experimentally demonstrated lytic activity of the Chilean P. verruculosa ARC498 strain toward the RTgill-W1 cells, although ecologically realistic P. verruculosa bloom concentrations (10,000-100,000 cells ml −1 ) exhibited only very limited loss of viability (down to max.…”
Section: Lytic Activity Of P Verruculosamentioning
confidence: 81%
“…, Dorantes‐Aranda et al. ); (ii) production of mucus by fish due to the presence of H. akashiwo cells; fish mucus has been shown to increase ROS production by raphidophytes in a concentration‐dependent manner that could enhance ROS‐mediated toxicity (Nakamura et al. , Kim and Oda ), and potentially explain the lesions observed on affected fish gills (Chang et al.…”
Section: Discussionmentioning
confidence: 99%
“…This is in concordance with the recent findings of Dorantes‐Aranda et al . (). Other products assayed were disinfectants (i.e.…”
Section: Chemical and Physical–chemical Methodsmentioning
confidence: 97%